2013
DOI: 10.1684/pnv.2013.0391
|View full text |Cite
|
Sign up to set email alerts
|

Influenza and pneumococcal vaccine coverage among patients admitted to an acute geriatric unit

Abstract: Malgré les stratégies thérapeutiques préventives disponibles, les patients âgés sont particulièrement touchés par les infections grippales et pneumococciques et les conséquences sont souvent lourdes dans cette population fragile. L'objectif de cette étude était d'évaluer la couverture vaccinale des patients admis en service de court séjour gériatrique et les caractéristiques des patients les mieux vaccinés. Nous avons donc mené une étude observationnelle prospective auprès de 149 patients admis dans ce type de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…In the literature, other similar studies reported coverage ranging from 58%-73% for influenza and of approximately 50% for pneumococcus, substantially higher than our coverage. [6][7][8] It is necessary to underline that these surveys regarded elderly people, whereas our study is focused on children and adults and that the framework for vaccination offer is quite different in Italy.…”
mentioning
confidence: 99%
“…In the literature, other similar studies reported coverage ranging from 58%-73% for influenza and of approximately 50% for pneumococcus, substantially higher than our coverage. [6][7][8] It is necessary to underline that these surveys regarded elderly people, whereas our study is focused on children and adults and that the framework for vaccination offer is quite different in Italy.…”
mentioning
confidence: 99%